Generation of Aryl Grignard Reagents from Arene Chromium Tricarbonyl Complexes by Mg(TMP)2·2LiCl and Their Application to Murahashi Coupling - Momoi, Yuichi; Okano, Kentaro; Tokuyama, Hidetoshi (Synlett, 2014)
A mild and straightforward synthesis of biaryls is described that is performed through direct arylation of the C–H bond of (arene)Cr(CO)3 upon deprotonation with Mg(2,2,6,6-tetramethylpiperazide)2·2LiCl and subsequent palladium-catalyzed cross-coupling reaction.
Keywords: chromium; copper; cross-coupling; magnesium; palladium